2007
DOI: 10.1007/s00122-007-0695-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a yield-enhancing QTL cluster associated with transgressive variation in an Oryza sativa × O. rufipogon cross

Abstract: A high-resolution physical map targeting a cluster of yield-related QTLs on the long arm of rice chromosome 9 has been constructed across a 37.4 kb region containing seven predicted genes. Using a series of BC3F4 nearly isogenic lines (NILs) derived from a cross between the Korean japonica cultivar Hwaseongbyeo and Oryza rufipogon (IRGC 105491), a total of seven QTLs for 1,000-grain weight, spikelets per panicle, grains per panicle, panicle length, spikelet density, heading date and plant height were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 35 publications
3
87
0
4
Order By: Relevance
“…In other words, QTL for yield may result from pleiotropic QTL: genomic regions that affect multiple traits by containing multiple, tightly linked, trait-specific genes or genes that affect multiple traits (Hall et al 2006). Most published fine-mapped QTL and the genes identified as affecting yield exhibit pleiotropic effects on at least one trait (Peng et al 1999;Brown 2002;Yuan et al 2002;Li et al 2004;Ashikari et al 2005;Waller et al 2005;Clark et al 2006;Tian et al 2006a;Cockram et al 2007) or multiple yieldassociated traits (Quarrie et al 2006;Xie et al 2006Xie et al , 2008Burstin et al 2007;Song et al 2007;Shomura et al 2008;Xue et al 2008). Even a short region with a confidence interval of 0.4 cM and a physical distance of 37.4 kb has revealed pleiotropic effects between seven QTL of different yield-associated traits and the QTL of grain yield in rice (Xie et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, QTL for yield may result from pleiotropic QTL: genomic regions that affect multiple traits by containing multiple, tightly linked, trait-specific genes or genes that affect multiple traits (Hall et al 2006). Most published fine-mapped QTL and the genes identified as affecting yield exhibit pleiotropic effects on at least one trait (Peng et al 1999;Brown 2002;Yuan et al 2002;Li et al 2004;Ashikari et al 2005;Waller et al 2005;Clark et al 2006;Tian et al 2006a;Cockram et al 2007) or multiple yieldassociated traits (Quarrie et al 2006;Xie et al 2006Xie et al , 2008Burstin et al 2007;Song et al 2007;Shomura et al 2008;Xue et al 2008). Even a short region with a confidence interval of 0.4 cM and a physical distance of 37.4 kb has revealed pleiotropic effects between seven QTL of different yield-associated traits and the QTL of grain yield in rice (Xie et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Yield-related traits (such as biomass, harvest index, plant architecture, adaptation, resistance to biotic and abiotic constraints) may also indirectly affect yield by affecting the yield-component traits or by other, unknown mechanisms. Increasing evidence suggests that ''fine-mapped'' quantitative trait loci (QTL) or genes identified as affecting crop yield involve diverse pathways, such as seed number (Ashikari et al 2005;Tian et al 2006b;Burstin et al 2007;Xie et al 2008;Xing et al 2008;Xue et al 2008), seed weight (Ishimaru 2003;Song et al 2005;Shomura et al 2008;Wang et al 2008;Xie et al 2006Xie et al , 2008Xing et al 2008;Xue et al 2008), flowering time (Cockram et al 2007;Song et al 2007;Xie et al 2008;Xue et al 2008), plant height (Salamini 2003;Ashikari et al 2005;Xie et al 2008;Xue et al 2008), branching (Clark et al 2006;Burstin et al 2007;Xing et al 2008), biomass yield (Quarrie et al 2006;Burstin et al 2007), resistance and tolerance to biotic and abiotic stresses (Khush 2001;Brown 2002;Yuan et al 2002;Waller et al 2005;Zhang 2007;Warrington et al 2008), and root architecture (Hochholdinger et al 2008).…”
mentioning
confidence: 99%
“…The most persuasive explanation for the phenomenon may be pleiotropism, or a closely-linked relationship between genes controlling the different traits. For example, a total of seven QTLs for 1000-grain weight, spikelets per panicle, grains per panicle, panicle length, spikelet density, heading date, and plant height in rice generated one cluster (P≤0.0001) and were co-localized in the same 37.4 kb interval (Xie et al 2008). Most of the wall-associated kinase (WAK) /WAK-like kinase (WAKL) family also display gene clusters (Verica andHe 2002), andHe et al (2006) found a leucine-rich repeat receptor kinase gene cluster underlying a single QTL for yield-related traits in rice (He et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TAC1, a gene responsible for controlling tiller angle, was cloned at 23.9 Mb (Yu et al 2007). Although clear evidence for the association between TAC1 and QTLs related to grain yield and drought tolerance has not been obtained (one QTL for yield has been mapped near but not at the TAC1 locus; Xie et al 2008), TAC1 might be detected as a QTL for those traits because tillering angle can affect photosynthetic ability and thus be associated with yield potential and drought tolerance.…”
Section: Distribution Of Qtl Clusters In the Rice Genome Mapmentioning
confidence: 99%